Empathy, Kindness, and Moderation are not Just Formalities in Science - Rovetta, Alessandro; Castaldo, Lucia (Information & Media, 2024)
Science is a systematic approach to building and organizing knowledge through testable explanations and predictions. However, since scientists are human beings, they are fallible and subject to various systematic and random biases. The COVID-19 pandemic has definitively unmasked the humanity of scientists, who committed severe communication mistakes or even adhered to conspiracy hypotheses. Indeed, emotionality and rationality (if not epistemic) can foster intellectual dishonesty and compromise the effectiveness of critical thinking. This highlights the importance of the context in which a scientist works, as politeness and respect are essential to maintain lucidity, credibility, and transparency. However, outside of the academic context, many scientists do not behave with the same level of courtesy and carefulness required in scientific publishing. This happens despite communication – which is crucial for scientific investigation, dissemination, and debunking campaigns – being scientifically based on compassion. Specifically, an effective communication plan should be tailored to a specific audience, taking into account their emotional state, cultural and social background, and cognitive and psychological characteristics. The sole purpose must be to help and not to manipulate. Therefore, empathy, kindness, and moderation are essential tools for the success of science, from research to communication and education, and awareness campaigns and training courses should be instituted to promote such a message.